Scent of apples : a collection of stories - Santos, Bienvenido N. (Seattle ; London : University of Washington Press, 2015)
This collection of sixteen stories bring the work of a distinguished Filipino writer to an American audience. Scent of Apples contains work from the 1940s to the 1970s. Although many of Santos's writings have been published in the Philippines, Scent of Apples is his only book published in the United States.--Back cover.
COVER -- TITLE -- COPYRIGHT -- CONTENTS -- FOREWORD: MY LOST COUNTRY -- INTRODUCTION TO THE 2015 EDITION: FOOTNOTE TO MEMORY -- INTRODUCTION TO THE 1979 EDITION -- PREFACE TO THE 1979 EDITION -- IMIGRATION BLUES -- SCENT OF APPLES -- AND BEYOND, MORE WALLS -- THE HURT MEN -- MANILA HOUSE -- A PECULIAR RUSTLING -- NIGHTCLUB -- OF OTHER DEATHS -- LONELY IN THE AUTUMN EVENING -- THE DOOR -- FOR THESE RUINS -- LETTER: THE FARAWAY SUMMER -- THE DAY THE DANCERS CAME -- THE CONTENDER -- QUICKER WITH ARROWS -- FOOTNOTE TO A LAUNDRY LIST.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Filipino Americans -- Fiction; Américains d'origine philippine -- Romans, nouvelles, etc; FICTION -- General; FICTION -- Asian American; Filipino Americans; Fictional Work; Fiction; Fiction; Romans